2019
DOI: 10.1111/medu.13821
|View full text |Cite
|
Sign up to set email alerts
|

Debunking the myth that the majority of medical errors are attributed to communication

Abstract: Context Many articles, book chapters and presentations begin with a declaration that the majority of medical errors are attributed to communication. However, this statement may not be supported by the research reported in the literature. Objectives The purpose of this systematic review is to identify where errors are reported in the research literature. Methods A systematised review was conducted of research articles over the last 20 years (1998‐2018) indexed in PubMed/MEDLINE and the Cumulative Index to Nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 46 publications
(85 reference statements)
1
28
0
5
Order By: Relevance
“…Beyond prolonged reaction to an automation failure, failing to act may be attributed to both commission and omission errors [23,24,28].Errors of commission happen when the HITL makes a mistake or error due to incorrect decision-making. Errors of omission occur when the human does nothing when they should have [24,29].…”
Section: Complacencymentioning
confidence: 99%
“…Beyond prolonged reaction to an automation failure, failing to act may be attributed to both commission and omission errors [23,24,28].Errors of commission happen when the HITL makes a mistake or error due to incorrect decision-making. Errors of omission occur when the human does nothing when they should have [24,29].…”
Section: Complacencymentioning
confidence: 99%
“…Analyses of adverse events and other critical incidents commonly identify communication failures between healthcare providers as major contributing factors. [1][2][3][4] Standardised, structured communication techniques have emerged as a potential solution to these recurring problems. 5 6 The mnemonic SBAR (situation, background, assessment, recommendation) constitutes the most well-known such technique.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, medical error has become the third major cause of death following cardiac disease and cancer [5]. Several root cause analyses performed revealed that medical errors are mostly attributed to errors of commission, omission, and communication [6]. Debriefing offers a healthcare team the opportunity to re-examine the clinical encounter, discuss individual and team performance, identify errors, and develop performance improvement strategies through reflective learning processes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%